2012
DOI: 10.1002/anie.201207491
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Designing a Concave Pt–Ni Alloy through Controllable Chemical Etching

Abstract: This corrosion: Octahedral Pt-Ni alloy nanoparticles (NPs) are converted into concave Pt(3)Ni NPs by a coordination-assisted chemical-etching process. The corroded concave Pt-Ni NPs have a higher density of low-coordinate atoms in steps sites, a decisive property in heterogeneous catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 27 publications
4
142
2
Order By: Relevance
“…Key strategies to reduce Pt contents involve alloying Pt with other transition metal [3][4][5][6][7][8] , de-alloying non-precious metal to obtain a Pt rich shell [9][10][11] and core-shell-structured nanoparticles [12][13][14][15] . These approaches, to some degree, increase Pt utilization, but cannot fully solve the problem of Pt dependence.…”
mentioning
confidence: 99%
“…Key strategies to reduce Pt contents involve alloying Pt with other transition metal [3][4][5][6][7][8] , de-alloying non-precious metal to obtain a Pt rich shell [9][10][11] and core-shell-structured nanoparticles [12][13][14][15] . These approaches, to some degree, increase Pt utilization, but cannot fully solve the problem of Pt dependence.…”
mentioning
confidence: 99%
“…For instance, our group presented a controllable "top-down" synthesis of concave Pt-Ni alloys which exhibited higher catalytic activity compared to the uncorroded alloys through a coordination assisted chemical-etching process (Fig. 23) [383]. Coordinating agent (dimethylglyoxime) with the presence of oxygen was used to control the chemical etching process at room temperature to synthesize a concave structure.…”
Section: Shape Controlmentioning
confidence: 99%
“…Driven by the difference in the chemical reactivity of two metallic species, the dealloying process has gained great success in constructing hollow [505], porous [506], concave [383,507] and frame structures [238] with fascinating geometrical beauty and interesting chemical and physical properties. The generated reactive sites such as interior vacancies and surface defects are strictly related to the dissolution of more active metals and rearrangement of the reserving residue.…”
Section: Top-down and Bottom-upmentioning
confidence: 99%
“…In 2012, Li's group reported that a concave octahedral Pt-Ni alloy with a Pt-segregated surface can be constructed using a controlled dealloying process [3]. This work has led to the effective design of nanosegregated Pt skins on Pt-based bimetallic nanoalloys using a simple wet-colloid method.…”
Section: Science China Materialsmentioning
confidence: 99%
“…They showed that the surface steps in the Pt 3 Ni concave hexapod alloy formed in the initial stage of the synthesis were crucial in the segregation of an M-rich (M = Ni, Co, etc.) phase in the Pt-Ni alloy through step-induced deposition.…”
mentioning
confidence: 99%